The Nigerian foreign exchange market & finance of international trade - Ovwielefuoma, Godwin (Lagos, Nigeria : Mike-Win Publishers Nigeria, 1988)
This books focuses on Foreign exchange, international trade every other components of financial market.
Bibliography: p. 220
osa; 20/6/17
Loans
Keywords: Foreign exchange - Law and legislation; Foreign trade regulation; Foreign exchange administration - Nigeria; Nigeria - Commerce - Finance; Foreign trade regulation - Nigeria